2005
DOI: 10.4028/www.scientific.net/msf.492-493.189
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Corrosion Resistance of Multi-Layered Ti/Glass-Ceramic Interfaces by Electrochemical Impedance Spectroscopy

Abstract: Practical applications of metal/ceramic joints can be found in the biomedical field regarding the encapsulation of implantable telemetric devices, the fabrication of crowns and bridges for dental restoration, or in the production of drug delivery systems, biomedical sensors and electrodes. Most of metal/ceramic joints are produced by the active metal brazing technique, which originates a multi-layered interface which should be able of accommodating the abrupt electronic, crystallographic, chemical, mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…High levels of hardness observed (1500HV) near the glass-ceramic interface [11] was attributed to the formation of intermetallics between titanium and SiO2 of glass-ceramic. The corrosion test of the MACOR ® to Ti joint was performed by some researchers [12,13] and it was observed that an AgCl layer was formed due to reaction with the braze alloy which acts as a passive film to prevent the degradation of joint. Liu et al [14] successfully brazed SiO2 glass ceramic and Ti6Al4V alloy with the help of Ti active metal braze alloy.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of hardness observed (1500HV) near the glass-ceramic interface [11] was attributed to the formation of intermetallics between titanium and SiO2 of glass-ceramic. The corrosion test of the MACOR ® to Ti joint was performed by some researchers [12,13] and it was observed that an AgCl layer was formed due to reaction with the braze alloy which acts as a passive film to prevent the degradation of joint. Liu et al [14] successfully brazed SiO2 glass ceramic and Ti6Al4V alloy with the help of Ti active metal braze alloy.…”
Section: Introductionmentioning
confidence: 99%
“…In this equivalent model, Rs is the solution resistance; Rp stands for the resistance of the sample in the solution, and CPE1 counts for the constant phase element corresponding to the capacitance of the corrosion pits. As the most important characteristic of all the EIS value, the polarization resistance Rp represent the resistant ability to against the corrosion [12,13]. Table 5 shows all the values of equivalent circuit elements of the cladding samples in 3.5% NaCl solution.…”
Section: Electrochemical Analysismentioning
confidence: 99%